Comparison of tonsillectomy by coblation and tonsillectomy by conventional method - Karathia, Neha Mihir; Kansara, Atul H. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Operations on tonsils and adenoids are performed since many years. Tonsillectomy produces an open wound that heals by secondary intention. Tonsillectomy is still a very common surgical procedure. There are various modalities to perform surgery (diathermy, laser, harmonic scalpel, radiofrequency cautery, cryosurgery and coblation). Among these, dissection and snare method are commonly done by ENT surgeons. Methods: We carried out the prospective cross-sectional study to compare intraoperative blood loss, time taken for the surgery, post-operative pain score, degree of slough formation and complications between these two methods. Results: Average time for surgery on coblation side was less (15.1 min) than conventional side (36.04 min). For haemostasis on conventional side, all patients required bipolar cauterization while on coblation side only 8 patients (16%) required hemostasis. Average blood loss on coblation side (left) was 3.40ml while on conventional side (right) 25.57 ml. In my study, mean pain score on 1st day, 2nd day, 5th and 10th day of surgery was 6.18, 4.10, 2.30 and 1.64 on conventional side and 4.36, 3.00, 1 and 0 on coblation side. In my study, only one patient had Secondary haemorrhage on conventional side on 7th day. Conclusions: The use of coblator reduces the time required for surgery, per-operative blood loss is very much less, chances of damage to surrounding structures are less, charring of tissue is less, post-operative severity of pain after 24 hours is very much less than that of dissection method. Slough formation was more on coblation side as compared to conventional side.